3.3V DC output at -16dBm sensitivity and 77% PCE rectifier for RF energy harvesting - Astrie Nurasyeila Fifie Asli; Yan Chiew Wong (Institute of Advanced Engineering and Science, 2019)
This paper presents a high voltage conversion at high sensitivity RF energy harvesting system for IoT applications. The harvesting system comprises bulk-to-source (BTMOS) differential-drive based rectifier to produce a high efficiency RF energy harvesting system. Low-pass upward impedance matching network is applied at the rectifier input to increase the sensitivity and output voltage. Dual-oxide-thickness transistors are used in the rectifier circuit to maintain the power efficiency at each stage of the rectifier. The system is designed using 0.18µm Silterra RF in deep n-well process technology and achieves 4.07V output at -16dBm sensitivity without the need of complex auxiliary control circuit and DC-DC charge-pump circuit. The system is targeted for urban environment.